Aromatic amino acid biosynthesis in the yeast Saccharomyces cerevisiae: a model system for the regulation of a eukaryotic biosynthetic pathway. - Braus, G H (1991)
This review focuses on the gene-enzyme relationships and the regulation of different levels of the aromatic amino acid biosynthetic pathway in a simple eukaryotic system, the unicellular yeast Saccharomyces cerevisiae. Most reactions of this branched pathway are common to all organisms which are able to synthesize tryptophan, phenylalanine, and tyrosine. The current knowledge about the two main control mechanisms of the yeast aromatic amino acid biosynthesis is reviewed. (i) At the transcriptional level, most structural genes are regulated by the transcriptional activator GCN4, the regulator of the general amino acid control network, which couples transcriptional derepression to amino acid starvation of numerous structural genes in multiple amino acid biosynthetic pathways. (ii) At the enzyme level, the carbon flow is controlled mainly by modulating the enzyme activities at the first step of the pathway and at the branch points by feedback action of the three aromatic amino acid end products. Implications of these findings for the relationship of S. cerevisiae to prokaryotic as well as to higher eukaryotic organisms and for general regulatory mechanisms occurring in a living cell such as initiation of transcription, enzyme regulation, and the regulation of a metabolic branch point are discussed.